العمران الوقفي في الغرب الإسلامي (5-9ه/11/15م) - محمدو, ولد همر (Universty of Eloued جامعة الشهيد حمة لخضرالوادي, 2023)
الملخص: عرفت منطقة الغرب الإسلامي خلال الفترة الممتدة من بداية القرن الخامس إلى نهاية التاسع الهجري ( 111- 15م) انتشارا كبيرا لظاهرة الأوقاف وكانت وراء انتشارها جملة من الأسباب الدينية والضرورات الثقافية والحربية للحواضر الإسلامية، أملت على المجتمع ولا سيما أصحاب رؤوس الأموال والسلاطين جعل بعض ممتلكاتهم أوقافا، فكان منها جانب مخصص للمساجد والمرابطين في الربط والحصون، وجانب مخصص لعمارة المدارس والقائمين على الزوايا الصوفية. وقد تنوعت هذه الموقوفات؛ حيث شملت الأراضي الزراعية وعقارات أخرى متعددة إلى جانب الأموال والأشجار المثمرة والسواني المائية. الكلمات المفتاحية: النوازل – الغرب الإسلامي - الدور الموقوفة – المنشآت الدينية - الممتلكات الوقفية – الشواهد الأثرية Abstract : The Western Islamic region witnessed a significant spread of the endowment phenomenon during the period from the beginning of the fifth century to the end of the ninth Hijri century (11-15 CE). This spread was influenced by a combination of religious reasons, cultural necessities, and the military needs of Islamic cities. It inspired the community, especially the wealthy and the rulers, to establish some of their properties as endowments. These endowments included designated areas for mosques and those stationed in connecting routes and fortresses, as well as areas dedicated to building schools and supporting Sufi lodges. These endowments varied and encompassed agricultural lands, various other properties, as well as money, fruit-bearing trees, and water channels. Keywords: Nwazel, Western Islamic, endowed buildings, religious institutions, endowed properties, historical artifacts.
دراسة من خلال النوازل والشواهد الأثرية
أطروحة دكتوراه تخصص تاريخ وسيط في العلوم الاجتماعية و الانسانية
Keywords: النوازل – الغرب الإسلامي - الدور الموقوفة – المنشآت الدينية - الممتلكات الوقفية – الشواهد الأثرية; Nwazel, Western Islamic, endowed buildings, religious institutions, endowed properties, historical artifacts.